2009
DOI: 10.3181/0904-mr-134
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nanomaterial Surfaces for Biomedical Applications

Abstract: Nanomaterials, possessing unique physical and chemical properties, have attracted much interest and generated wide varieties of applications. Recent investigations of functionalized nanomaterials have expanded into the biological area, providing a versatile platform in biomedical applications such as biomolecular sensing, biological imaging, drug delivery and disease therapy. Bio-functions and bio-compatibility of nanomaterials are realized by introducing synthetic ligands or natural biomolecules onto nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 120 publications
(114 reference statements)
1
106
0
1
Order By: Relevance
“…To date, great attention is focused on the development of highly specific adsorbent materials, namely materials with great affinity towards CO 2 molecules (Choi et al, 2009). Sure enough, the scientific community is moving in this direction, putting the emphasis on the manufacture of designed nanomaterials in which a molecular level of control can be achieved as a means of tailoring their CO 2 capture performance (Wang et al, 2009;Dawson et al, 2013;Baxter et al, 2009). However, although certain attributes of solid sorbents prove to be promising, they must still be integrated into a viable process (D'Alessandro et al, 2010) which includes the implementation of equipment that can take full advantage of the sorbent properties and maximize the separation efficiency (Sjostrom et al, 2011;Yang et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…To date, great attention is focused on the development of highly specific adsorbent materials, namely materials with great affinity towards CO 2 molecules (Choi et al, 2009). Sure enough, the scientific community is moving in this direction, putting the emphasis on the manufacture of designed nanomaterials in which a molecular level of control can be achieved as a means of tailoring their CO 2 capture performance (Wang et al, 2009;Dawson et al, 2013;Baxter et al, 2009). However, although certain attributes of solid sorbents prove to be promising, they must still be integrated into a viable process (D'Alessandro et al, 2010) which includes the implementation of equipment that can take full advantage of the sorbent properties and maximize the separation efficiency (Sjostrom et al, 2011;Yang et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization of nanomaterials includes simple or complex physical or chemical procedures that involve weak electrostatic repulsion, hydrogen bonding, hydrophobic interactions or covalent bonds, respectively (Wang et al 2009). One study showed that coating SPIONs with a gold layer enabled subsequent functionalization with thiolated DNA, which could then remain stable in aqueous solution (Robinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic properties such as Surface Plasmon Resonance (SPR) of Ag, Au metallic nanoparticles (NPs) can be exploited for biosensing, drug delivery, bioimaging; fluorescence and luminescence of semiconductor CdS, CdSe NPs for immunoassays, bioimaging, biosensing; magnetism of magnetic Fe3O4 for MRI, drug delivery; electronic, mechanical and conductivity of carbon nanotubes (CNTs), and fullerene for drug, gene delivery, therapy and biosensing [9].…”
Section: -18 Nmmentioning
confidence: 99%